Inclusion of Polypills for Prevention of Cardiovascular Disease in the 23rd World Health Organization Model List of Essential Medicines: A Significant Step Towards Reducing Global Cardiovascular Morbidity and Mortality - Agarwal, Anubha; Huffman, Mark D. (Global heart, 2024)
This commentary describes the potential impact of inclusion of polypills for prevention of cardiovascular disease in the 23rd WHO Model List of Essential Medicines, and provides a roadmap for adoption, implementation, sustainment, and scale-up. The World Health Organization's endorsement of polypills is essential for improving global access, particularly in low- and middle-income countries. The greatest health gains are expected in a primary prevention population which has a significantly higher burden of fatal and non-fatal cardiovascular disease compared with the population of individuals with prevalent cardiovascular disease. A focus on adoption, implementation, sustainment, and scale-up of polypills for prevention of cardiovascular disease is needed including increasing supply of available polypills and incorporating polypills into the World Health Organization HEARTS technical package for integration into primary care systems to realize these benefits for population health. Widespread implementation of polypills for prevention of cardiovascular disease has the potential to equitably reduce the impact of cardiovascular disease globally by simplifying treatment options and expanding accessibility across economic levels, both across and within countries.